Bacterial growth on the hands of health care workers: implications for preventing nosocomial infections - Ana Beatriz Silva de Andrade; Larissa Sousa Oliva Brun; Priscila Brandão; Maithê de Carvalho e Lemos Goulart; Cristiane Albuquerque de Carvalho; Fernanda Maria Vieira Pereira Ávila (Universidade Federal do Ceará, 2021)
Objective: to analyze bacterial growth in samples collected from the hands of health professionals after hygiene with soap and water. Methods: cross-sectional analytical study, carried out with healthcare professionals by collecting samples (print) from the digital pulp of the dominant hand on plates containing chromogenic culture medium for microbiological analysis regarding the presence of colonies. Fisher's and Chi-square tests were used. Results: 73 samples were collected and 67 (91.8%) showed bacterial growth. Methicillin-resistant Staphylococcus aureus was detected in 19 (26.0%). A significant association between colonies with multidrug-resistance profile and the time of performance (p=0.030) and profession (p=0.041) was highlighted. Conclusion: there was bacterial growth in samples after hand hygiene, with higher growth of multidrug-resistant bacteria among nursing professionals and those with longer time of work. These results may contribute to detect the gaps about the measures adopted for infection prevention.